Digital Economy Transformation: The Potential of Digital Transactions in Developing Small and Medium Enterprises in Palu City - Suwedy; Arnianti; Mutmainah (Universitas Muhammadiyah Palu, 2025)
This study introduces a digital economy perspective that focuses on digital transactions in developing a business, especially Small and Medium Enterprises (SMEs) in Palu City. The method used in this study is quantitative with a causal associative approach to determine the relationship and influence between exogenous variables (digital transactions) on endogenous variables (income level). The population of this study, namely SMEs in West Palu District, totaled 288, while the determination of the sample in this study used a census. The sampling technique is the purposive sampling technique, the number of samples obtained is 197 SMEs, while 91 SMEs do not meet the criteria that have been determined. The findings of this study are that digital transactions have a significant influence on the income level of a Small and Medium Enterprises (SMEs) in West Palu District, Palu City. Another finding is that digital transactions have a strong relationship with income levels.